Sunshine Trading: Flashes of Trading Intent at the NASDAQ - Johannes A. Skjeltorp; Elvira Sojli; Wing Wah Tham (Tinbergen Institute, 2012)
We use the introduction and the subsequent removal of the flash order facility (an actionable indication of interest, IOI) from the NASDAQ as a natural experiment to investigatethe impact of voluntary disclosure of trading intent on market quality. We find that flashorders significantly improve liquidity in the NASDAQ. In addition, overall market qualityimproves substantially when the flash functionality is introduced and deteriorates when it isremoved. One explanation for our findings is that flash orders are placed by less informedtraders and fulfill their role as an advertisement of uninformed liquidity needs. They successfully attract responses from liquidity providers immediately after the announcement isplaced, thus lowering the risk-bearing cost for the overall market. Our study is important inunderstanding the impact of voluntary disclosure, in guiding future market design choices,and in the current debate on dark pools and IOIs.
urn:NBN:nl:ui:15-1765/38217
Keywords: G10; G20; G14; 330; Actionable Indication of Interest (IOI); Flash orders; High-frequency Trading; Spekulation; Marktliquidität; Finanzmarktregulierung; Aktienmarkt; USA